Effect of Asana Pranayama Yoga on Sleep Quality: Implications for Stress Management and Healthy Lifestyle in Young Adults - Adella, Abigail Sherolyn; Lilis, Lilis; Sudiyono, Nelson; Cahyadi, Alius; Gracia, Isadora (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Sleep is a fundamental human need. Young adults, such as medical students, are particularly vulnerable to poor sleep quality due to the academic pressures. Yoga has a relaxing effect that may help improve sleep quality. This study aimed to evaluate the effects of Asana Pranayama yoga on sleep quality among female medical students.Methods: This quasi-experimental and case-control study was conducted in September 2023, including preclinical female medical students from the Atma Jaya Catholic University of Indonesia. Sleep quality was assessed using the Indonesian version of the Pittsburgh Sleep Quality Index (PSQI-I). The intervention group (n=24) had performed yoga Asana Pranayama six times per week for four weeks, with each session lasting 45 minutes, whereasthe control group had received no intervention. Data were analyzed using the Wilcoxon signed-rank test to compare pre- and post-intervention PSQI scores, and Spearman’s correlation to examine the relationship between yoga frequency and PSQI scores (p<0.05).Results: The intervention group showed a significant improvement in sleep quality (p=0.002). A significant negative correlation was found between yoga practice frequency and post-test PSQI scores (r=-0.607), indicating that higher consistency in yoga practice was associated with better sleep quality.Conclusion: Regular practice of asana pranayama yoga can improve sleep quality among female medical students. Incorporating yoga into daily routines may serve as a practical, non-pharmacological approach to promote wellness in young adults.